2007
DOI: 10.1127/1863-9135/2007/0168-0271
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of freshwater crabs (Potamonautes spp.) in rivers draining Mt Kenya, East Africa

Abstract: Little is known about population densities of freshwater crabs, or their ecological importance, in African rivers. This study aimed to quantify crab abundance in rivers draining Mt Kenya. Invertebrates were sampled from 21 sites on 19 rivers. Sample sites were divided into: open sites in agricultural land from which trees were mainly absent; shaded sites, in agricultural land, with cultivated catchments but heavy shading by riparian trees; and forest sites, still dominated by natural vegetation. Crabs, mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…This may be especially true in the tropics, where many shredders have large body sizes, e.g., shrimps (March et al 2001), crabs (Dobson 2004) or semi-terrestrial cockroaches (Yule et al 2009). We did not measure biomass, but note that the shredders that we recorded in PAN and AWT were not especially large in comparison with those of temperate streams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be especially true in the tropics, where many shredders have large body sizes, e.g., shrimps (March et al 2001), crabs (Dobson 2004) or semi-terrestrial cockroaches (Yule et al 2009). We did not measure biomass, but note that the shredders that we recorded in PAN and AWT were not especially large in comparison with those of temperate streams.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that other macroinvertebrates or insect orders occupy the shredder feeding guild. These include crabs in Kenya (Dobson 2004), crayfish in Australia , shrimps in Puerto Rico (Greathouse & Pringle 2006), snails, crabs, mayflies and semi-terrestrial cockroaches in Malaysia (Yule et al 2009), and mayflies in Papua New…”
Section: Discussionmentioning
confidence: 99%
“…They are widely consumed by humans and act as an intermediate host for food-borne diseases such as paragonimiasis (Appleton, 2012). These crabs are ecologically important, as their role in decomposition of detrital matter, combined with their large abundance and biomass (Dobson et al, 2007;Klaus and Plath, 2011), makes them a critical component of nutrient recycling in their ecosystems and ideal for use as bio-indicators (Steenkamp et al, 1994;Reinecke et al, 2003). In addition to this, crabs form a spatial link between aquatic and terrestrial habitats as a result of their amphibious lifestyle (Morris and Van Aardt, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid Surber method may have worked well in the study streams as a consequence of the high population densities of crabs often encountered in African rivers (Dobson et al 2007b). However, the results obtained suggest that this method is worth considering in situations where rapid assessment is required and resources are limited.…”
Section: Discussionmentioning
confidence: 99%